Effects of Positive End-Expiratory Pressure and Spontaneous Breathing Activity on Regional Lung Inflammation in Experimental Acute Respiratory Distress Syndrome. Issue 4 (April 2019) - Kiss, Thomas; Bluth, Thomas; Braune, Anja; Huhle, Robert; Denz, Axel; Herzog, Moritz; Herold, Johannes; Vivona, Luigi; Millone, Marco; Bergamaschi, Alice; Andreeff, Michael; Scharffenberg, Martin; et al.
Abstract : Objectives: To determine the impact of positive end-expiratory pressure during mechanical ventilation with and without spontaneous breathing activity on regional lung inflammation in experimental nonsevere acute respiratory distress syndrome. Design: Laboratory investigation. Setting: University hospital research facility. Subjects: Twenty-four pigs (28.1–58.2 kg). Interventions: In anesthetized animals, intrapleural pressure sensors were placed thoracoscopically in ventral, dorsal, and caudal regions of the left hemithorax. Lung injury was induced with saline lung lavage followed by injurious ventilation in supine position. During airway pressure release ventilation with low tidal volumes, positive end-expiratory pressure was set 4 cm H2 O above the level to reach a positive transpulmonary pressure in caudal regions at end-expiration (best-positive end-expiratory pressure). Animals were randomly assigned to one of four groups ( n = 6/group; 12 hr): 1) no spontaneous breathing activity and positive end-expiratory pressure = best-positive end-expiratory pressure – 4 cm H2 O, 2) no spontaneous breathing activity and positive end-expiratory pressure = best-positive end-expiratory pressure + 4 cm H2 O, 3) spontaneous breathing activity and positive end-expiratory pressure = best-positive end-expiratory pressure + 4 cm H2 O, 4) spontaneous breathing activity and positive end-expiratory pressure = best-positive end-expiratory pressure – 4 cm H2 O. Measurements and Main Results: Global lung inflammation assessed by specific [ 18 F]fluorodeoxyglucose uptake rate (median [25–75% percentiles], min –1 ) was decreased with higher compared with lower positive end-expiratory pressure both without spontaneous breathing activity (0.029 [0.027–0.030] vs 0.044 [0.041–0.065]; p = 0.004) and with spontaneous breathing activity (0.032 [0.028–0.043] vs 0.057 [0.042–0.075]; p = 0.016). Spontaneous breathing activity did not increase global lung inflammation. Lung inflammation in dorsal regions correlated with transpulmonary driving pressure from spontaneous breathing at lower ( r = 0.850; p = 0.032) but not higher positive end-expiratory pressure ( r = 0.018; p = 0.972). Higher positive end-expiratory pressure resulted in a more homogeneous distribution of aeration and regional transpulmonary pressures at end-expiration along the ventral-dorsal gradient, as well as a shift of the perfusion center toward dependent zones in the presence of spontaneous breathing activity. Conclusions: In experimental mild-to-moderate acute respiratory distress syndrome, positive end-expiratory pressure levels that stabilize dependent lung regions reduce global lung inflammation during mechanical ventilation, independent from spontaneous breathing activity. Abstract : Supplemental Digital Content is available in the text.